The Clergy as Advocates for the Severely Demented - Lapsley, James N. (Journal of pastoral care & counseling, 2002)
The author sets forth the argument that pastoral caregivers ought to consider expanding their traditional role of ministering to dementia patients by pressing the issue of whether appropriate medication might significantly lessen the suffering of these persons. After discussing and documenting the current understanding regarding the nature of pain, the author outlines several advocacy, ethical, and procedural issues that could be included in providing pastoral care to this population, at the same time not minimizing more traditional faith-based activities.